2016
DOI: 10.1128/jvi.02171-15
|View full text |Cite
|
Sign up to set email alerts
|

Pan-ebolavirus and Pan-filovirus Mouse Monoclonal Antibodies: Protection against Ebola and Sudan Viruses

Abstract: The unprecedented 2014-2015 Ebola virus disease (EVD) outbreak in West Africa has highlighted the need for effective therapeutics against filoviruses. Monoclonal antibody (MAb) cocktails have shown great potential as EVD therapeutics; however, the existing protective MAbs are virus species specific. Here we report the development of pan-ebolavirus and pan-filovirus antibodies generated by repeated immunization of mice with filovirus glycoproteins engineered to drive the B cell responses toward conserved epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 48 publications
(68 reference statements)
4
87
0
3
Order By: Relevance
“…FVM04 binds to a conformational epitope within the core of GP1 (residues 31 to 200), a region that encompasses the RBR and the base of GP1 (22). While previous reports of antibodies targeting the GP1 core indicated that epitopes in this region are likely concealed (16,19; also see the accompanying article by Holtsberg et al [42]), the FVM04 binding profile was not significantly changed upon removal of the MLD, suggesting that the epitope of FVM04 is well exposed and likely on the top of the trimeric GP chalice. Interestingly, FVM01p, another MAb that strongly bound the GP1 core, failed to protect mice, indicating that the specificity of the epitope is critical for protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FVM04 binds to a conformational epitope within the core of GP1 (residues 31 to 200), a region that encompasses the RBR and the base of GP1 (22). While previous reports of antibodies targeting the GP1 core indicated that epitopes in this region are likely concealed (16,19; also see the accompanying article by Holtsberg et al [42]), the FVM04 binding profile was not significantly changed upon removal of the MLD, suggesting that the epitope of FVM04 is well exposed and likely on the top of the trimeric GP chalice. Interestingly, FVM01p, another MAb that strongly bound the GP1 core, failed to protect mice, indicating that the specificity of the epitope is critical for protection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to determine whether combination of our pan-ebolavirus antibodies that bind to novel epitopes will lead to enhanced efficacy compared to individual MAbs. To this end, we tested two different combinations: (i) FVM02p and FVM09, targeting the fusion loop and glycan cap, respectively; and (ii) FVM09 and m8C4, a mouse pan-ebolavirus antibody (see the accompanying article by Holtsberg et al [42]), which binds to a conformational epitope involving the glycan cap. Both of these combinations provided 100% protection against lethal challenge although the antibodies were administered at a lower dose compared to the study with individual antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, pan-Ebolavirus monoclonal antibodies with demonstrated in vitro activity have been identified (32)(33)(34), and these experimental candidates could be screened in ferrets in vivo. Other advantages with using ferrets as a potential animal model include better availability, smaller body sizes, less stringent housing requirements, and reduced costs.…”
Section: Discussionmentioning
confidence: 99%
“…In comparisons of the vaccine efficacy of wild-type and N-linked-glycan-deficient glycoproteins, the amount of the different pseudovirions administered in each vaccine study was adjusted for GP equivalents. To quantify this, purified pseudovirions were serially diluted, and proteins were separated by SDS-PAGE, transferred to nitrocellulose, and probed with anti-EBOV GP monoclonal antibody 21D10 (72) and VSV matrix (M) 23H12 (73). 21D10 recognizes filovirus GP residues 81 to 89, a region of GP that does not contain N-linked glycosylation and so should recognize the denatured GPs equivalently.…”
Section: Methodsmentioning
confidence: 99%